Pengaruh Ekstrak Etanol Daun Rhizophora apiculata terhadap Kolesterol Total dan Trigliserida Rattus norvegicus Galur Sprague dawley yang Diinduksi Diet Tinggi Lemak - Syazili Mustofa; Farhan Kamali Adli; Dyah Wulan Sumekar Rengganis Wardani; Hendri Busman (Jurnal Kesehatan, 2022)
Dyslipidemia is a lipid metabolism disorder in the form of an increase and decrease in the lipid fraction which is one of the high-risk factors for coronary heart disease and other non-communicable diseases. Rhizophora apiculata contains secondary metabolites in the form of flavonoid, tannin, alkaloid, saponin, and terpenoid which are thought to have the effect of preventing an increase in total cholesterol and triglyceride. This research is an experimental study with a posttest-only control group design carried out for 30 days using 30 experimental animals of Rattus norvegicus Sprague Dawley. There were 6 treatment groups, KN which was only given standard feed, K+ which was given quail egg yolk induction, simvastatin 10 mg/day, and K- which was given quail egg yolk induction. On the other hand, P1, P2, and P3 were given quail egg yolk induction, respectively. and leaf extract of Rhizophora apiculata with doses of 56mg/KgBW,m28mg/KgBW, and 14mg/KgBW. Then the rats were terminated using ketamine xylazine and blood was taken through the heart to be examined for total cholesterol and triglyceride using spectrophotometry. The results of the normality Shapiro-Wilk and Levene test p-value>0.05. In the One-way Anova test, cholesterol levels were 0.006 and triglyceride 0,002 (p-value